Analysis of Anies Rasyid Baswedan's Political Rhetoric in the 2017 Jakarta Gubernatorial Election (Oratio Directa, 2024)
Rhetoric is closely related to a person's ability to speak before an audience. In the 2017 Jakarta gubernatorial election, debate forums gave candidates an opportunity to attract public sympathy and political support through effective rhetoric. This study analyzes how Anies Rasyid Baswedan used Aristotle's rhetorical concepts and invitational rhetoric in debates organized by the Jakarta General Elections Commission. The qualitative study applies rhetorical analysis to digital-trace documentation obtained from debate recordings on CNN Indonesia's YouTube channel. The findings show that Anies effectively used ethos, pathos, and logos and applied an audience approach based on equality, immanent value, and self-determination. These strategies attracted sympathy and political support and contributed to his victory in the 2017 Jakarta gubernatorial election.
Keywords: Political rhetoric; Anies Baswedan; Ethos; Pathos; Logos